ANALYZING STUDENTS' PASSIVE VOICE DIFFICULTIES - Muziatun Muziatun; Fahria Malabar; Lisnawati Mustapa (Indonesian EFL Journal, 2022)
The purpose of this study is to find out how difficult it is for students of using passive voice. There were twenty students in class B of the English Department's 2017 academy class at University Negeri Gorontalo, but only sixteen of them were chosen for this study, which employed a descriptive quantitative technique. A survey and an interview were used to get the data. As part of the test, students had to change the forms of numerous active sentences into passive ones. The data was examined using Sudijono’s (2006) formula and Parrot's (2000) theory of passive voice difficulties. This study found that students in the English Department's Class of 2017 at Universitas Negeri Gorontalo continue to struggle with the use of the passive voice. Auxiliary verb "be" utilization was found to be the most problematic by students admitted, with a percentage of 67.18 percent, followed by difficulties in changing the main verb into the past participle (48.43 percent) and changing the object and subject (43.75 percent). The usage of the auxiliary verb "be" is the most difficult part of passive voice for students, compared to the other two.Keywords: students’ difficulties; grammar; and passive voice.